Assessment of the Efficiency of Government Healthcare Expenditure in Selected European Union Member States: A DEA Approach - Цоклинова, Мая (Научни трудове, 2025)
The aim of this article is to assess the efficiency of expenditure of the sector “General Government” for the “Healthcare” function in the member states of the European Union (EU). To achieve this aim, the non-parametric method of data envelopment analysis (Data Envelopment Analysis (DEA)) is applied, oriented towards the input with variable returns to scale. The study uses the expenditure of the sector “General Government” for the “Healthcare” function per capita as input resource, and the indicators “life expectancy” and “mortality per 100,000 people due to non-contagious diseases, infectious diseases and unclearly diagnosed diseases” as output results. Since, historically, the EU member states have been characterized by different economic development, two relatively homogeneous groups of countries have been distinguished. The first includes the so-called „old” member states, and the second includes countries from Central and Eastern Europe (CEE). The conclusion that follows is that the final results for the „old” member states, and in particular Austria, Belgium, Germany, Finland, France and Italy, as well as for the CEE countries - Estonia, Latvia, Lithuania, Hungary and the Czech Republic, could be achieved with fewer input resources. The latter is reason to seek opportunities for optimizing the healthcare systems of the analyzed countries.